The Construction of Body Image Scale in Early Adult Women - Kuncoro, Prayogo Agus; Salsabila, Savara; Puspitasari, Elysa Diana; Rahmawati, Annisa; Cahyani, Dewi Agus; Kurniawan, Fredirikus Bayu; Husna, Aftina Nurul (Prosiding University Research Colloquium, 2021)
The purpose of this research is to develop the right instrument to measure body image. Body image is a picture held in the mind of an individual about the size, shape, and individual feelings about the characteristics and body parts that make up the individual. In McCabe’s theory, there are five dimensions/aspects of body image: Body Image Importance, Body Concealment, Body Improvement, Social Physicue Anxiety, Appearance Comparison. The participants involved in the scale trial that the researchers conducted were 60 participants. Data was collected through an online survey. The sampling technique used was non-random sampling with Snowball-Sampling. Psychometric test results show that, the value of Cronbach’s Alpha which shows the number 0.909 out of 20 items, which means this measuring instrument has good reliability. Correlation Item-Total Statistics shows the correlation between one item and another item is more than 0.30.